Evaluation of uterine condom catheter tamponade in management of atonic postpartum haemorrhage in poor responders to medical management - Aggarwal, Aditi; Gupta, Ashoo; Mahajan, Puneeta; Zala, Ketan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Postpartum haemorrhage is major cause of obstetric morbidity and mortality. It is estimated that worldwide, 1 woman dies every 4 minutes due to postpartum haemorrhage. The incidence is said to be approximately 4% in vaginal deliveries and 7% in caesarean deliveries. The most common cause of postpartum haemorrhage is uterine atony which accounts for 80% cases of PPH. In patients poorly responding to medical management and before major surgical intervention and hysterectomy is envisaged, uterine tamponade is reasonable option for management of PPH. The condom catheter has been shown to be effective in managing severe PPH, and is a simple, cheap and quick intervention which may prove valuable in resource-poor countries. However, limited data is available regarding efficacy of uterine condom catheter tamponade. In this study, authors hypothesized that uterine condom catheter tamponade will reduce the need for surgical intervention by 70±10% for management of atonic PPH in patients who respond poorly to medical management. Methods: Prospective data of 26 women who went into atonic Primary PPH was collected over period of one year. Results: Out of 26 women who had atonic PPH, 12 were inserted with condom balloon catheter after medical management. Success rate was 11/12 (91.7%). Conclusions: Authors conclude that uterine condom catheter tamponade is 91.7% effective in controlling atonic postpartum haemorrhage poorly controlled with medical management, and hence is effective in averting laparotomy on 91.7% such patients.